The study of early complications among premature infants in the Division of premature and newborn Assad University Hospital in Lattakia - Jouni, Oday; Ganm, Abd almunam; Ali, Mais (Latakia University Journal -Medical Sciences Series, 2018)
The importance of studies in preterm infants has increased in recent years due to increased awareness of the subject of prematurity and the increase in the proportion of premature births in communities, especially in the presence of fertility means, treatment of infertility in couples and increased birth of twins. A statistical study was carried out for 110 preterm infant who entered the incubators of Al-Assad University Hospital between 2014-2015. The recovery period ranged from several hours to 40 days. 42% of neonates were hospitalized for a period of 1 to 7 days, 40% were hospitalized for less than one month. The mortality rate was 30% of the studied cases, of which 63.6% were males and the rest were females, mostly of the early type (during the first week) 72.7% and the rest of the late type (after the first week). The most important early complications developed by neonates during the study period: Septicemia 30%, Respiratory distress syndrome 30,6%, bacterial meningitis 2.7%, Pneumonia 13.6%, pulmonary hemorrhage 12.2%, Apnea 22.4%, intraventricular hemorrhage 13%, hemorrhage Cerebral parenchyma 8.7%, cerebrovascular estrogen 8.7%, survival of isolated arterial artery 5.5%, PDA with pulmonary hypertension 18.8%, intestinal inflammation and colon necrosis 18.8%, upper gastric hemorrhage 11%, hypotension Blood glucose 11.8%, hypo calcemia 7.3%. دراسة الاختلاطات الباكرة لدى الخدج في شعبة الخديج والوليد في مشفى الأسد الجامعي في اللاذقية لقد ازدادت أهمية الدراسات المجراة لدى الخدج في السنوات الأخيرة وذلك بسبب زيادة الوعي حول موضوع الخداج, وزيادة نسبة الولادات المبكرة في المجتمعات وبخاصة بوجود وسائل الإخصاب ومعالجة العقم لدى الأزواج وزيادة ولادة التوائم. تم إجراء دراسة إحصائية ل 110وليد خديج دخلوا حاضنات مشفى الأسد الجامعي بين عامي 2014-2015. تراوحت فترة الإستشفاء بين عدة ساعات حتى 40يوم. 42% من الولدان استشفوا لفترة بين يوم وأسبوع, 40% استشفوا أقل من شهر. شكلت نسبة الوفيات 30% من الحالات المدروسة,منهم 63,6% ذكور والبقية إناث, معظمها من النوع الباكر (خلال أول أسبوع) 72,7%, والبقية من النوع المتأخر(بعد الأسبوع الأول). أما أهم الاختلاطات الباكرة التي طورها الولدان خلال فترة الدراسة: انتان دم 30%, داء أغشية هلامية 30,6%, التهاب سحايا جرثومي 2,7%, ذات رئة 13,6%, نزف رئوي 12,2%, نوب توقف تنفس 22,4%, نزف ضمن البطينات 13%, نزف ضمن البارانشيم الدماغي 8,7%, استسقاء دماغ 8,7%, بقاء قناة شريانية معزول 5,5%, PDA مع فرط توتر رئوي 18,8%, التهاب أمعاء وكولون نخري 18,8%, نزف هضمي علوي 11%, نقص غلوكوز الدم 11,8%, نقص كالسيوم الدم 7,3%.